Analisis Penerapan Software Pada Pelatihan Pembukuan Laporan Keuangan Sederhana Bagi KPM Oleh BBPPKS - Bryan Wicaksono; Reni Yendrawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
UMKM have a very important role for the advancement of a country's economic growth. There are lots of Indonesian people who become UMKM principals, but not all of them are categorized in KPM. Some UMKM that meet the requirements can be categorized as KPM. These UMKM also really need training in applying financial records in accordance with the currently applicable Accounting Standards, namely Financial Accounting Standards. This has the aim of helping UMKM that are included in the KPM category implement financial records that are in accordance with SAK UMKM, especially using the Microsoft Excel system. The PKH team that has been given training by BBPPKS is now required to provide training to KPM regarding procedures for recording financial bookkeeping which later can be practiced by KPM in order to facilitate their business in the financial sector. Sources of data collected based on interviews with several interrelated parties in the preparation of this report, as well as some other supporting data. The research results show that the UMKM studied have not implemented financial bookkeeping which will later be used to record financial reports and make decisions. It is recommended that UMKM that are categorized in the KPM category can apply this excel-based financial bookkeeping application, and take advantage of the convenience in this application so that it can assist users in preparing financial reports and also make it easier for users to calculate their business profits.